Analisis Pendapatan Di Sektor Pertambangan dan Indeks Pertumbuhan Ekonomi Terhadap Pertumbuhan Ekonomi Di 8 Kabupaten Di Kalimantan Selatan - Haris, Muhammad; Sopiana, Yunita (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
The aim of this research was to find out whether Income in the Mining Sector, Average Years of Schooling, Budget Surplus, and Democracy Index influence Economic Growth in 8 Districts in South Kalimantan Province. This research is quantitative in nature using secondary data, namely 2009-2020 panel data which was calculated using Panel Data Analysis through the Eviews 10 program. The research results show that Income in the Mining Sector, Average Years of Schooling, Budget Surplus, and Democracy Index simultaneously have a significant effect on Economic Growth. Meanwhile, partially there is a significant effect on the Average Years of Schooling variable. The magnitude of the influence of the variable is 53% while the remaining 47% is influenced by other variables outside the model.